MASTER: three heterodyne receivers for Millimetre and Submillimetre-wave astronomy - BATTISTELLI, Elia Stefano; ANDREONE D; BOELLA G; BRUNETTI L; CAVALIERE F; DE PETRIS, Marco; GERVASI M; LACQUANITI V; NATALE V; PASSERINI A; SIRONI G; STENI R; et al. (2001)
We describe a system of three heterodyne receivers for astrophysical observation at $94GHz$, $225GHz$ and $345GHz$ through the atmospheric windows available at dry, high altitude sites (Italian Alps, Antarctic Plateau). Three $SIS$ mixers, fed by geometrically scaled corrugated horns, oriented in the same direction, form the core of our system. The four beams (HPBWs $sim 7^{circ}$) are optimized for matching the focus of the $MITO$ or sub-mm wave telescopes. The intermediate frequency ($IF$) signal produced by each mixer is $1.5GHz$, with an instantaneous bandwidth of $pm0.4GHz$. Each receiver is mechanically tunable over a total bandwidth of $pm1GHz$ at $94GHz$, $pm2.5GHz$ at $225GHz$ and $pm4GHz$ at $345GHz$. The $SIS$ mixer and the first $IF$ amplifier are cooled at $4K$ and the expected noise temperature of the system are between $100K$ and $170K$. The local oscillator and cold load reference signals are injected into the horns by a diplexer and mirror combinations. Rotation of a mirror modulates the system output for synchronous detection. An acousto-optical system at the $IF$ output is used for spectroscopic observation.